Centers of psycho-social attention and the strategies for family insertion - Schrank, Guisela; Olschowsky, Agnes (Revista da Escola de Enfermagem da USP, 2008)
This research has the objective of identifying the mental health activities developed at Centers of Psycho-Social Attention (CAPSs) directed to the family in the care of individuals in psychological suffering. It is a descriptive, analytic survey of the case study type with a qualitative approach. Data collection was carried out through observation and semi-structured interviews with professionals of a CAPS. The results showed that the work at a CAPS becomes successful only when there is family partnership and participation. Individual sessions, family groups, active searches, home visits and workshops are strategies used at CAPSs for the effective insertion of the family. In this partnership, bonding appears as essential in the construction of less suffering and less stigmatized ways of psychical suffering.